2018
DOI: 10.1124/pr.117.014977
|View full text |Cite
|
Sign up to set email alerts
|

International Union of Basic and Clinical Pharmacology CIV: The Neurobiology of Treatment-resistant Depression: From Antidepressant Classifications to Novel Pharmacological Targets

Abstract: Major depressive disorder is one of the most prevalent and life-threatening forms of mental illnesses and a major cause of morbidity worldwide. Currently available antidepressants are effective for most patients, although around 30% are considered treatment resistant (TRD), a condition that is associated with a significant impairment of cognitive function and poor quality of life. In this respect, the identification of the molecular mechanisms contributing to TRD represents an essential step for the design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 406 publications
(436 reference statements)
1
41
0
3
Order By: Relevance
“…A closely related phenomenon seems to be "resistance" to antidepressant treatment. As noted, there are many drivers of treatment resistance in depression [27], with a number of clinical factors identified by the studies GSRD (European Group for the Study of Resistant Depression) [28,29] including, but not limited to, psychiatric and general medicine comorbidities, and a number of clinical-demographic variables affecting the lifetime course and current status of depression, as reviewed by Caraci F. et al, 2018 [30]. In 1984, Lieb and Balter [31] described the emergence of refractoriness in some patients with MDD to drugs for depression that had been previously efficacious.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A closely related phenomenon seems to be "resistance" to antidepressant treatment. As noted, there are many drivers of treatment resistance in depression [27], with a number of clinical factors identified by the studies GSRD (European Group for the Study of Resistant Depression) [28,29] including, but not limited to, psychiatric and general medicine comorbidities, and a number of clinical-demographic variables affecting the lifetime course and current status of depression, as reviewed by Caraci F. et al, 2018 [30]. In 1984, Lieb and Balter [31] described the emergence of refractoriness in some patients with MDD to drugs for depression that had been previously efficacious.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(a) Duration is scored 1-3 corresponding to acute (<1 year), subacute (1 to <2 years), and chronic (>2 years); (b) severity is scored 1-5 corresponding to subsyndromal, mild, moderate, severe without psychosis, and severe with psychosis; and (c) treatment strategies are scored 1-5 with regard to antidepressants (level 1: 1-2 medications; level 2: 3-4 medications; level 3: 5-6 medications; level 4: 7-10 medications; and level 5: >10 medications), plus 0 or 1 with regard to pharmacological augmentation strategy, and plus 0 or 1 with regard to ECT. Study participants were categorized as resistant (7)(8)(9)(10)(11)(12)(13)(14)(15) or nonresistant (3-6) according to their total MSM score.…”
Section: Assessment Proceduresmentioning
confidence: 99%
“…Several sociodemographic, clinical, and neurobiological factors have been associated with the presence of treatment resistance in depression. A recent review by Caraci et al [7], which includes the study performed by the European Group for the Study of Resistant Depression, reported several clinical features significantly associated with treatment resistance. These variables were comorbid psychiatric disorders, suicide risk, severity and duration of current episode, number of hospitalizations, depressive recurrences, melancholic and psychotic features, nonresponse to a first antidepressant treatment, occurrence of side effects during treatment, lower age at onset, high occupational level, and family psychiatric history.…”
Section: Introductionmentioning
confidence: 99%
“…The S-3 guidelines from the Association of Scientific Medical Societies in Germany (AWMF) [3] recommend pharmacological and behavioral interventions for mild to moderate depression and electroconvulsive therapy (ECT) as the standard treatment for more severe and chronic symptomology. About 20-30% of patients receiving common, pharmacological treatments, do not respond to the intervention or develop side effects [4,5]. Furthermore, a treatment resistant depression has been associated with significant alterations of cognitive functions and even suicidal attempts [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…About 20-30% of patients receiving common, pharmacological treatments, do not respond to the intervention or develop side effects [4,5]. Furthermore, a treatment resistant depression has been associated with significant alterations of cognitive functions and even suicidal attempts [5,6]. This might reflect a need for effective alternative treatments or interventions to complement common clinical practice.…”
Section: Introductionmentioning
confidence: 99%